2018
DOI: 10.1097/aud.0000000000000671
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Cochlear Implantation for Single-Sided Deafness: Data From the House Clinic-University of Southern California-University of California, Los Angeles Clinical Trial

Abstract: Objectives: Cochlear implants (CIs) have been shown to benefit patients with single-sided deafness (SSD) in terms of tinnitus reduction, localization, speech understanding, and quality of life (QoL). While previous studies have shown cochlear implantation may benefit SSD patients, it is unclear which point of comparison is most relevant: baseline performance before implantation versus performance with normal-hearing (NH) ear after implantation. In this study, CI outcomes were assessed in SSD patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
104
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(116 citation statements)
references
References 62 publications
11
104
1
Order By: Relevance
“…There are six subcategories: emotional and cognitive distress, intrusiveness, auditory perceptual difficulties, sleeping disturbances, somatic complaints, and total score. There are four tinnitus severity levels: low (score 1-30), moderate (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46), severe (47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), and very severe (60-84).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are six subcategories: emotional and cognitive distress, intrusiveness, auditory perceptual difficulties, sleeping disturbances, somatic complaints, and total score. There are four tinnitus severity levels: low (score 1-30), moderate (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46), severe (47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59), and very severe (60-84).…”
Section: Methodsmentioning
confidence: 99%
“…The tinnitus prevalence in previous SSD studies was in the range 46.4% to 90.9%. 2,13,28 There are several studies that reported a positive influence of CI on tinnitus distress in SSD patients 4,5,[26][27][28][29]41,42 ; however, in some studies there are heterogeneous groups with patients with SSD and asymmetric hearing loss, and there is no standardized test used for the evaluation of tinnitus distress.…”
Section: Tinnitus Distressmentioning
confidence: 99%
“…2 Most studies have found that patients with single-sided deafness have poor sound localisation abilities and reduced speech perception abilities in noisy environments due to only receiving unilateral input. 1,[4][5][6] Traditionally, the contralateral routing of signal ('CROS') hearing aid, which was first introduced by Harford and Barry in 1965, was used to improve hearing in patients with single-sided deafness. 7 Many patients complain that the contralateral routing of signal device causes poor sound quality, discomfort and occlusion in the normal ear.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that cochlear implantation devices used in adults with single-sided deafness significantly decrease tinnitus and improve localisation, speech perception in noise and QoL. 1,4,6,18 Similarly, some children with single-sided deafness have obtained significant audiological and subjective benefits from cochlear implantation. 4,5,19 Unlike the contralateral routing of signal and BAHA devices, cochlear implantation helps patients with single-sided deafness obtain bilateral input and restores bilateral hearing, rather than simply transmitting sound signals to the normal ear.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators feel that cochlear implants are superior to other devices, such as devices for contralateral routing of sound (CROS) and osseointegrated implants, for stimulating the deaf ear rather than send sounds to the opposite ear, but there are still some controversies in relation to these opinions. [2][3][4][5][6][7] According to Dillon et al, 8 cochlear implantation in cases of substantial hearing loss may offer significant improvements in the quality of life; quality of life measures revealed a reduction in perceived tinnitus severity and subjective improvements in speech perception in noise, spatial hearing, and listening effort.…”
Section: Introductionmentioning
confidence: 99%